INDEPENDENT CURRICULUM ASSESSMENT: IMPLEMENTATION AND OBSTACLES IN ARTS AND CULTURE SUBJECTS AT SMAIT AL MUMTAZ PONTIANAK - Mega Cantik Putri Aditya (Sean Institute, 2023)
The aim of this research is to determine the implementation of the independent curriculum assessment at SMAIT Al Mumtaz Pontianak. Curriculum changes affect aspects of learning assessment carried out by educators, both formative and summative. Thus, it cannot be denied that there are still many teachers who do not optimally understand the implementation of assessments, which will have an impact on obstacles to achieving Learning Objectives (TP). Several teachers at SMAIT Al Mumtaz experienced this problem. This research method is descriptive qualitative, the method used aims to find out more deeply with the teacher about the implementation of the assessment, starting from planning, implementation and results. Data collection techniques consist of observation, interviews and documentation studies. The research informants consisted of three teachers and two students. The results of this research are the implementation of diagnostic and non-diagnostic assessments, both formative and summative. The implementation uses rubrics and descriptions to measure TP achievement and provide feedback information for teachers to improve the learning process. The achievement scale is 90-100 and must repeat 80-90. Meanwhile, in summative implementation of PTS and PAS, students are divided into 3 grades, namely 3 levels. These levels consist of ABCD or levels 1,2,3. The obstacles that teachers face are that they still need training in strategies to overcome students' difficulties in achieving TP, and the time constraints required to improve grades. In differentiated learning, teachers continue to guide medium and low students and not all students belonging to the advanced group are confident in providing understanding to students in the medium or low category. Then students spend more money on intracurricular and co-curricular activities to obtain grades. Activities that have been carried out, such as the Arts, Culture and Skills Workshop, are a big activity for the school to showcase students' work, namely producing local content using natural materials and simple used goods into useful items with a touch of the typical cultural identity of the city of Pontianak.